The Influence Of Social Media Marketing And Brand Engagement On Brand Awareness And Brand Image (Case Study On Brownis Ingsun Products On The Account @sorgumnesia.official) - Cindy Clarissa Quenby; Nurul Azizah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Social Media Marketing and Brand Engagement have an important role for business which has an impact on Brand Awareness and Brand Image. This research aims to identify the influence of social media marketing and brand engagement on brand awareness and brand image (case study of the brownis ingsun product on the @sorgumnesia.official account). The population in this research are Instagram followers @sorgumnesia.officia and consumers who have purchased products from Sorgumnesia, namely "Brownis Ingsun". This research sample consisted of 120 respondents selected using purposive sampling technique. The data presentation technique used is quantitative. The data analysis technique uses multiple linear regression analysis. The results of this research show that Social Media Marketing partially has a significant effect on Brand Awareness, Brand Engagement partially has a significant effect on Brand Awareness, Social Media Marketing partially has no significant effect on Brand Image, Brand Engagement partially has a significant effect on Brand Image, and Brand Awareness partially has a significant effect on Brand Image. Then, Social Media Marketing and Brand Engagement simultaneously have a significant effect on Brand Awareness and Social Media Marketing and Brand Engagement simultaneously have a significant effect on the Brand Image of Brownis Ingsun Products on the @sorgumnesia.official account.